Local Wisdom of the Cireundeu Traditional Village as a Learning Resource in History Education - Farhan Nur Ghifari; Diana Mutiarani; Leli Yulifar (Historia, 2027)
History learning at the high school level is still driven by teacher-centered lectures and nation-centric textbooks, so students often struggle to understand the relevance of history to their lives. This study aims to identify forms of local wisdom in the Cireundeu Traditional Village, particularly within the local food security system, and to analyze their relevance as a source of history learning in CP Phase E of the Independent Curriculum in high schools. The study employed a qualitative approach using ethnographic methods, including participant observation, in-depth interviews, and document analysis, conducted in April 2026 in the Cireundeu Traditional Village. The results show that the local wisdom of the Cireundeu Traditional Village is multidimensional, encompassing cassava-based food security and rasi, cultural inheritance systems, the traditional Ngemban Taun ritual, as well as the Ngantereuran tradition, which has been practiced since 1918. All of these dimensions are relevant to the material on historical research steps and historical sources in CP Phase E and meet the criteria for economical, practical, flexible, and relevant learning resources.